Woven generalized fusion frame in Hilbert $C^{*}-$module (Jurnal Matematika, Statistika dan Komputasi, 2022)
The notion of weaving was recently proposed to simulate a question in distributed signal processing and wireless sensor networks.In this paper we introduced the notion of a woven $g-$fusion frame in Hilbert $C^{*}-$modules, also we gives some properties. Finallly we study perturbation of weaving $g-$fusion frames.
Keywords: Fusion frame; g-fusion frame; woven g-fusion frame; $C^{*}$-algebras; Hilbert $C^{*}$-modules